ASSESSMENT OF THE STATE OF RECREATIONAL INFRASTRUCTURE IN MOUNTAINOUS AREAS OF LVIV REGION - Lopotych Н.; Shkumbatiuk О.; Verkhola Г. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
The article presents the findings of scientific studies focused on the transformation processes occurring in the mountainous districts of Lviv region. It highlights the profound changes in indigenous vegetation and land use in the area, which have severely impacted environmental stability and diminished the appeal of tourism and recreational lands. To counteract these negative effects, economic incentives aimed at the conservation and restoration of native vegetation and soil are essential for stabilizing the environment. Additionally, promoting and economically developing the tourism and recreation infrastructure, especially with the gradual easing of international borders and improved governance, could alleviate the long-standing stagnation faced by mountain communities in Lviv. This study assesses the condition of recreational infrastructure in the mountainous areas of Lviv region, an important factor in the advancement of the region’s tourism sector. It evaluates key components of this infrastructure, including hotels, tourist bases, hiking and cycling routes, as well as sites of cultural heritage. Employing statistical analysis methods and field research, the study determines the level of infrastructure development, measuring its alignment with contemporary standards and tourist needs. The findings reveal that, despite the region’s natural resources and recreational potential, significant challenges persist, such as inadequate funding, low service quality, and insufficient promotional efforts. To enhance the state of recreational infrastructure, the article proposes several recommendations, including the development of government support programs, attracting investment, and fostering collaboration between state institutions and private enterprises. Implementing these measures could not only elevate the quality of tourist services but also promote the sustainable development of the mountainous areas of Lviv region as a whole.